Studies on stomatal frequency and its relationship with leaf biomass and rhizome yield of turmeric (Curcuma longa L.) genotypes - De, B Panja, D K (Journal of Spices and Aromatic Crops, 2001)
Stomatal frequencies of twelve turmeric (Curcuma longa L.) genotypes were recorded from different locations of both surfaces of the fourth, sixth and eighth nodal leaves. Turmeric leaves were amphistomatous having lower stomatal frequency in the upper surface (426.6 - 1773.7 sq. cm-1) and higher in the lower surface (7131.5 - 12,270.9 sq. cm-1) of the leaves. With a few exceptions, stomatal frequency of the leaves of the genotypes tested increased from fourth to eighth nodal position. The stomatal frequency of the genotypes either at the same location within leaf, at different locations within leaf or both leaf surfaces taken together did not vary significantly. The genotype TCP-9 had the highest stomatal frequency. However, stomatal frequency increased from base towards tip on both surfaces of the leaf, irrespective of the position of the leaf in all the genotypes. The stomatal frequency appeared significant and more positively correlated with rhizome yield than leaf dry weight in genotypes resistant to leaf blotch disease while in susceptible types it exhibited significant and negative correlation with leaf dry weight and rhizome yield.